2016
DOI: 10.1007/s10265-016-0822-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing of Metrosideros polymorpha (Myrtaceae), a dominant species in various habitats in the Hawaiian Islands with remarkable phenotypic variations

Abstract: Whole genome sequences, which can be provided even for non-model organisms owing to high-throughput sequencers, are valuable in enhancing the understanding of adaptive evolution. Metrosideros polymorpha, a tree species endemic to the Hawaiian Islands, occupies a wide range of ecological habitats and shows remarkable polymorphism in phenotypes among/within populations. The biological functions of genetic variations observed within this species could provide significant insights into the adaptive radiation found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…The recognition site of MseI consists of only adenine and thymine (5 0 -T|TAA-3 0 ), whereas that of NlaIII consists of all nucleotides (5'-CATG|-3 0 ). Although the GC content in the whole genome is lower than 50% for many plants [50], Myrtaceae species also tend to exhibit low GC content [51,52]. Thus, these results showed that the varying number of integrated reads obtained when different restriction enzymes were used was reasonable.…”
Section: Effect Of Fragmentationmentioning
confidence: 80%
“…The recognition site of MseI consists of only adenine and thymine (5 0 -T|TAA-3 0 ), whereas that of NlaIII consists of all nucleotides (5'-CATG|-3 0 ). Although the GC content in the whole genome is lower than 50% for many plants [50], Myrtaceae species also tend to exhibit low GC content [51,52]. Thus, these results showed that the varying number of integrated reads obtained when different restriction enzymes were used was reasonable.…”
Section: Effect Of Fragmentationmentioning
confidence: 80%
“…The reads were mapped to the genome sequences of M. polymorpha (Izuno et al . ; DDBJ Accession BCNH01000001–BCNH01036376) using bowtie 2 (ver. 2.2.4; Langmead & Salzberg ) with default parameter settings.…”
Section: Methodsmentioning
confidence: 99%
“…To enhance the genomewide studies of M. polymorpha (2 n = 22), we recently reported a genome assembly (Izuno et al . ). By sequencing two paired‐end and nine mate‐pair libraries (up to 24‐kb insertion size), we obtained 304‐Mbp genome sequences.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The first genome assembly of M. polymorpha (version 1.0 hereon) was reported as 304 Mb sequences, half of which were composed of 19 scaffolds with >5 Mbp (Izuno et al 2016). On the assembly, RepeatMasker (Smit et al 2013) identified 4.1% of the bases to be associated with repeated sequences and transposable elements (TEs), based on the homology with Arabidopsis thaliana repeat sequences.…”
mentioning
confidence: 99%